Khaya senegalensis augments the antinociceptive actions of piroxicam in murine models of hyperalgesia - Olurishe, T.O; Ishaq, F.N.; Zezi, A.U. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
The increasing use of herbs alongside orthodox drugs, and the widespread use of Khaya senegalensis for its antinociceptive properties, necessitated investigation of the effect of the plant on piroxicam mediated antinociception in rodents. Carbohydrates, anthraquinones, tannins and saponins were found to be present, with the latter two being consistently present in plants with antinociceptive properties. At 200 and 400 mg/kg the ethanolic stembark extract of Khaya senegalensis exhibited antinociceptive properties (p<0.05). The effect of piroxicam was enhanced in the acetic acid, formalin and carrageenan models. In the acetic acid model, the co administration of the extract with piroxicam resulted to a slightly greater inhibition of writhing than piroxicam alone. In the formalin test, there was also enhanced analgesia in the group that received the extract and piroxicam in comparison to piroxicam alone. In the carrageenan induced inflammation model, the effect of the extract and piroxicam both alone and together produced significant (p<0.05) reduction in paw edema from the second hour in comparison with piroxicam. A similar effect was observed in the chronic inflammatory model in mice. The concurrent administration of Khaya senegalensis and piroxicam showed synergistic antinociceptive effects. New chemical entities with analgesic effects that may be combined with NSAIDS reducing propensity for current toxicities may be explored from the plant.